The behaviour of a low- to medium-density chalk under a wide range of pressure conditions - Tingfa Liu; Pedro M.V. Ferreira; Ken Vinck; Matthew R. Coop; Richard J. Jardine; Stavroula Kontoe (Soils and Foundations, 2023)
Experiments are described which provided the basis for advanced numerical modelling of large-scale axial and lateral pile tests undertaken chalk to assist the design of offshore wind and other projects in northern Europe. The research explored the mechanical behaviour of chalk from a UK research site under effective cell pressures up to 12.8 MPa. When sheared from low confining pressures the chalk’s interparticle bonds contribute a large proportion of the peak deviator stresses available to specimens that crack, bifurcate and dilate markedly after failing at relatively small strains. Progressively more ductile behaviour is seen as pressures are raised, with failures being delayed until increasingly large strains and stable critical states are attained. Loading invokes very stiff responses within the chalk’s (Y1) linear elastic limits and behaviour remains stiff, although non-linear, up to large-scale (Y3) yield points. Near-elliptical Y1 and Y3 yield loci can be defined in q-p′ stress space and a critical state v-p′ curve is identified. The chalk’s initially bonded, high porosity, structure is explored by normalising the shearing and compression state paths with reference to both critical state and intrinsic compression lines. The results have important implications for pile test analysis and practical design in this challenging geomaterial.